HUBUNGAN KEPUASAN KERJA HUBUNGAN KEPUASAN KERJA DENGAN KINERJA PEGAWAI DI RUMAH SAKIT UMUM SEMBIRING KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2018 - ROBINSON PAULINUS SIHOMBING (Jurnal Kajian Kesehatan Masyarakat, 2020)
Job Satisfaction is the pleasure feeling of someone that affected to working activity with hope. Factors that can provide employee satisfaction are incentives, rewards, motivation, praise and others. By giving a sense of satisfaction, eill it certainly increase work productivity. The purpose of this study is to know the influences of job statisfaction to word the staff performance at Sembiring Hospital Deli Tua in 2018. This type of study is analytical with cross Sectional design. Population in this study is all Administration employees at Sembiring Deli Tua General Hospital as many as 76 employees and this research use total sampling that is 76 employees. The results showed that of 76 employees based on job satisfaction based on 45 (59.2%), based on age > UMR of 22 (28.9%), based on incentives of < Rp 500.000 as much as 42 (55.3%) and based on good results performance of 49 (64.5%). There is Influence of job to employee performance (p 0,001), There is atribute to employee performance (p 0,002). The most influential variable is job satisfaction variable with Exp (B) value of 0.170. It is hoped for Hospitals to more aspects of job satisfaction such as incentives, motivations, or individual contributions to improve employee performance to create exellent service and support better work.